Phidon chanco sp. nov. of cockroach from the coastal forest of central Chile (Insecta: Blattaria) - Vera S., Alejandro (Zootaxa, 2019)
Phidon chanco sp. nov. is the first species of the genus where both sexes are described Male and female genitalia are described and illustrated using SEM. The new species can be distinguished from the other members of the genus, by the existence of brachypterism in both sexes; in males the median triangle of the sternum IX is long, sclerotised, and its apex strongly armed with numerous denticles; in females the tergite X is emarginate. The new species is distributed exclusively in the coastal forests of central Chile, in association with remnants of native flora and protected areas.